THE EXTERMINATORS OF PRESENT: THE AGRAVATION OF THE PRECAURIOUS UBERIZED WORK CAUSED BY COVID- 19 PANDEMIC AND THE URGENT NECESSITY OF A REGULATING LEGISLATION. (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
The present work aims to analyze the aggravation of the precarious uberized work caused by the covid-19 pandemic, as well as demonstrate the urgent necessity of a regulating norm. However, to be able to comprehend, it is initially necessary to define the concept of uberization and the pros and cons of this phenomenon in the labor and social scope as a whole. Afterward, we move to the definition of what is the COVID-19 pandemic and how it worsened in Brazil, the precarious situation of the delivery motorcyclists work as well as transport drivers, primarily. Next, in the end we move to study the possibilities of regulating norms that can be utilized as means to guarantee basic labor and social rights to this class of workers. The present work shall demonstrate that there is a possibility of recognition of the employment relationship for these workers, and that in the actual prevailing law, there are already norms in which this work category fit, not necessarily demanding the creation of a new legislation for the situation to be regularized. Thus, it will be possible to conclude, that the biggest problem for the public authorities's inaction in relation to the problems of uberized work, do not reside in the lack of norm or impossibility of acknowledgement of the employment relationship, but in the lack of desire to change the scenery, subsidized by both political and juridic affairs. As for the method to be utilized, it will be based on bibliographic review, hypothetical-deductive approach, and in the study of case law regarding the theme.